4
$\begingroup$

I have to find the limit without L'hopital's rule: $$\lim_{x \to 0} \frac{\ln (x^2+1)} {x^2} $$

Is it possible? I thought about using squeeze theorem or something, but it didn't work out.

Hints are more than welcome!

P.S - I didn't study Taylor series or Integrals yet.

$\endgroup$
14
$\begingroup$

$$\begin{align} \lim_{x \to 0} \frac{\ln (x^2+1)} {x^2}&=\lim_{x \to 0} \ln (x^2+1)^{\frac{1}{x^2}}\\ &=\ln\left(\lim_{x \to 0} (x^2+1)^{\frac{1}{x^2}}\right)\\ &=\ln e=1 \end{align}$$

$\endgroup$
8
$\begingroup$

Let $f(u)=e^u$. With $t=\ln(x^2+1)$ we get

$$\lim_{x \to 0} \frac{\ln (x^2+1)} {x^2}=\lim_{t \to 0} \frac{t-0} {f(t)-f(0)}=\frac{1}{f'(0)}=1.$$

$\endgroup$
  • $\begingroup$ dear prof. Fred.. can you help me for ask limit Math question in stack.exchange??..Because this is so hard question for ask for me..And I can not turn the question into mathematics language..(+latex and english language)..Please..can you help me as your Little student.. :( I wrote on the paper and prepared direk link.. Can you look??.. :( $\endgroup$ – Mathematics is Life Aug 30 '17 at 9:44
4
$\begingroup$

If you know about equivalents, you have

$$\ln(x+1)\underset{x\to 0}{\sim}x$$

so

$$\ln(x^2+1)\underset{x\to 0}{\sim}x^2.$$

Therefore,

$$\lim_{x\to 0} \frac{\ln(x^2+1)}{x^2}=\lim_{x\to0} \frac{x^2}{x^2}=1.$$

$\endgroup$
  • 3
    $\begingroup$ You wrote: $\ln(x+1)\underset{x\to 0}{\sim}x$. But what does this mean ? It means that $\lim_{x \to 0} \frac{\ln (x+1)} {x}=1$. Therefore, you use what you want to proof ! $\endgroup$ – Fred Jan 26 '17 at 10:31
  • $\begingroup$ @Fred Yes, but I considered it a well know fact. Your proof of this statement below is great though. $\endgroup$ – E. Joseph Jan 26 '17 at 10:34
  • 1
    $\begingroup$ If $\lim_{x \to 0} \frac{\ln (x+1)} {x}=1$ is a well known fact, then $\lim_{x \to 0} \frac{\ln (x^2+1)} {x^2}=1$ is also a well known fact. $\endgroup$ – Fred Jan 27 '17 at 10:44
3
$\begingroup$

With series:

$ \ln(x^2+1)=x^2-\frac{x^4}{2}+\frac{x^6}{3}-+...$ for $|x|<1$,

hence

$\frac{\ln (x^2+1)} {x^2}=1-\frac{x^2}{2}+\frac{x^4}{3}-+... \to 1$ for $x \to 0$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.